2020
DOI: 10.1016/j.healthplace.2020.102398
|View full text |Cite
|
Sign up to set email alerts
|

An evidence-based theory of change for reducing SARS-CoV-2 transmission in reopened schools

Abstract: Schools have closed worldwide as part of measures to prevent SARS-CoV-2 transmission but are beginning to reopen in some countries. Various measures are being pursued to minimise transmission but existing guidance has not developed a comprehensive framework or theory of change. We present a framework informed by the occupational health hierarchy of control and a theory of change informed by realist approaches. We present measures focused on elimination, substitution, engineering, administration, education and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 40 publications
(65 reference statements)
0
47
0
4
Order By: Relevance
“…The repercussions of this preventive measure on educational and social development, wellbeing, and mental health were negative [24,25]. Although it has been concluded that the reopening of schools has not led to significant outbreaks or increased risk [26,27], some studies established that a return to the classroom must be accompanied by large-scale Test, Trace, and Isolate (TTI) systems [28] in order to prevent new waves.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The repercussions of this preventive measure on educational and social development, wellbeing, and mental health were negative [24,25]. Although it has been concluded that the reopening of schools has not led to significant outbreaks or increased risk [26,27], some studies established that a return to the classroom must be accompanied by large-scale Test, Trace, and Isolate (TTI) systems [28] in order to prevent new waves.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research and international guidelines published for schools' reopening [25,29] have determined the need to implement effective measures to minimise the risk of transmission, including an interpersonal distance of 2 m, face masks, frequent hygiene, temperature checks, and improved ventilation [23,24,30]. According to results, natural, hybrid, and mechanical ventilation systems can be used effectively and safely in schools, removing contaminated indoor air and supplying fresh outdoor air [26]. This preventive measure, along with the addition of filters, is a primary solution for the control of infectious diseases [31,32] and reduction of potential transmission [33].…”
Section: Introductionmentioning
confidence: 99%
“…To halt the COVID-19 pandemic, community members play the front-line practicing precautionary measures such as staying at home, physical distancing, appropriate utilization of personal protective equipment, and social assisting. 11 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…In Wuhan, China, a cluster of pneumonia cases caused by a novel coronavirus was identified as β-coronavirus on December 2019. 1,2 On 11 February 2020, the WHO officially named the disease coronavirus disease 2019 (COVID- 19) and declared the pandemic on March 12th, 2020. [3][4][5] Severe Acute Respiratory Syndrome Corona Virus 2 (SARS-CoV-2), a cause for COVID-19, is the seventh member of the family of coronavirus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation